Persuasive strategies of Jordanian government in fighting Covid-19 - Alkhawaldeh, Asim Ayed (Penerbit Universiti Kebangsaan Malaysia, 2021)
Since the outbreak of Covid-19 in March 2020 in Jordan that has continued to grow and impact all spheres of our lives, the government has been struggling to curb the pandemic through a range of safety and health measures. To this end, the government officials have employed diverse linguistic strategies in different media outlets to realize persuasion on the target audience in order to increase their awareness about the ongoing crisis and win public compliance and cooperation. Therefore, the present paper seeks, as its overriding goal, to explore the common linguistic strategies used by the Jordanian government to enhance its credibility and convince the public of the importance of effective adherence to its Covid-19 related policies (e.g. social distancing, face mask wearing, and self-hygiene). As an eclectic method of inquiry, the study draws generally on the perspective of discourse analysis and pragmatics. In addition, our analysis is informed by a corpus-based approach. The synthesis of our findings demonstrates that the government consistently and systematically utilizes various strategies for its persuasive intention (e.g. metaphor, repetition, and religious quotation). It also shows that the rationale beyond the respective persuasive techniques seems to win public compliance and cooperation, reassure the public, undermine opponent’s counterclaims, and project a trustworthy and praiseworthy image.